Tahapan Proses Produksi Dan Karakterisasi Bioplastik Dari Limbah Tongkol Jagung - Sumirat, Riska; Rosalinda, S.; Mardawati, Efri; Nurliasari, Desi; Kastaman, Roni (Politeknik Negeri Lampung., 2023)
Plastic is the dominant packaging used by the public, so it has the potential to damage the environment. It is necessary to synthesize raw materials for making plastics that are degraded by microorganisms, namely bioplastics. Bioplastics are packaging materials that are synthesized from natural raw materials so that they can be degraded in the environment. The raw material used is corncob because it is abundant and the benefits are not maximized. Research is needed to examine the stages of the production process and the characterization of bioplastics from corncob waste. The purpose of this study was to examine the stages of the production process and the characterization of bioplastics from corncob waste. This study used a laboratory experimental method with descriptive analysis. The production of bioplastics consists of the stages of making cellulose, cellulose acetate, and bioplastics using the solution casting method. The stages of cellulose isolation include hydrolysis, delignification, pulping, and bleaching, which showed an increase in cellulose content from 32.14% to 79.36%. Cellulose is acetylated to become cellulose acetate and has an acetyl content of 11.70 ± 0.40% with a yield of 121.16 ± 0.98%. The production of bioplastics uses a composition of cellulose acetate and chitosan at 50%:50% (w/w) successively. The resulting bioplastic has a thickness of 0.345 ± 0.024 mm, a density of 0.83 ± 0.03 g/cm3, a moisture content of 13.13%, a biodegradation value of 95.19%, a water resistance of 205.57%, and is transparent. The mechanical properties of bioplastics include a tensile strength of 22.3 N/m, an elongation of 21.11%, and a modulus of elasticity of 0.307 Mpa.